Nutrition Education Counseling for Breastfeeding Mothers and Healthy Toddlers is provided at the Bayangkari PC Health Center in South Tapanuli - Siti Alo Pasaribu; Mutia Sari Lubis; Hoirunnisa Tanjung; Tina Marito Harahap; Srianty Siregar; Izmi Fadhilah Nasution (CV Media Inti Teknologi, 2026)
Background: Proper nutrition during breastfeeding and early childhood is crucial for maintaining the mother's health, producing high-quality breast milk, and supporting the child's growth and development. In many areas, especially in Indonesia, many mothers and parents lack knowledge of how to prepare balanced meals. This lack of knowledge leads to nutritional problems, such as stunting, which is incredibly common.Objectives: This community service activity aimed to help breastfeeding mothers and parents of toddlers learn more about balanced nutrition through an educational program integrated with posyandu activities at the Bayangkari PC Posyandu in South Tapanuli Regency. The program covered topics such as the basics of balanced nutrition, nutritional needs during breastfeeding, the importance of exclusive breastfeeding, proper methods for introducing solid foods, and the use of locally available, nutritious foods.Methods: Activities were conducted using a participatory approach in which participants actively engaged through one-on-one conversations, group chats, planning healthy meals together, and pre- and post-session tests to assess learning.Results: The evaluation found that participants gained substantial knowledge from participating in educational activities. They learned more about selecting healthy, balanced foods, the benefits of exclusive breastfeeding, and the right ways to feed young children. They also became more confident in using good nutrition practices at home.Conclusion: Nutrition education delivered through integrated health service centers is effective in promoting healthy eating and preventing poor nutrition. It helps increase awareness about healthy eating among mothers and their families. This approach can also help make long-lasting improvements in children's eating habits and overall health.